1984
DOI: 10.1016/0375-9601(84)90941-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strong electric fields on exotic negative ions in He II: Possible evidence for the nucleation of charged vortex rings

Abstract: We present evidence suggesting that Ihas and Sanders' intermediate mobility exotic negative ions can nucleate quantised vortex rings in superfluid 4He when subjected to strong enough electric fields.Several years ago, Doake and Gribbon discovered [1] that there can exist in He II a fast ion which, unlike the normal negative ion [2], may be accelerated to the Landau critical velocity v L for roton creation without undergoing metamorphosis to a charged vortex ring, even under the saturated vapour pressure. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 5 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…[44][45][46] They, too, detected the fast ion and several of the exotic ions with different mobilities. In their measurements, the mobility in large electric fields was studied, whereas IS had investigated the mobility in low fields.…”
Section: )mentioning
confidence: 99%
“…[44][45][46] They, too, detected the fast ion and several of the exotic ions with different mobilities. In their measurements, the mobility in large electric fields was studied, whereas IS had investigated the mobility in low fields.…”
Section: )mentioning
confidence: 99%
“…In Ref. 5 their behavior has been tentatively attributed to a motion of an electron bubble undergoing a continuous sequence of escape-trapping-escape events of charged vortex rings.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Both fast and exotic ions under high electric fields have been studied in Ref. 5, where they found that the fast ions can reach the Landau critical velocity v L while the exotic ions decay instead into charged vortex rings before being able to reach v L .…”
Section: Introductionmentioning
confidence: 99%
“…Now the electron is liberated and free to be recaptured by vorticity elsewhere in the helium. Thus, while a decayingexponential drift velocity is consistent with the high field measurements of Eden and McClintock [11], the low field mobility would appear to lack the robust characteristics recently established by Maris and coworkers [1]. The most promising scenario then, of electron-vortex-bound states as the elusive fast and exotic ions, is for the electron to establish an equilibrium structure.…”
Section: Creation and Transport Of Electron-vortex-ring Bound Statesmentioning
confidence: 56%